Composition of mangrove and macrozoobenthos species ar Lhok Buon Beach, Samatiga District, West Aceh Regency - Wahyuni, Sri; Munandar, Munandar; Lisdayanti, Eka; Mursawal, Asri; Kurniawan, Ronal; Riswan, M. (Science, Technology, and Education Care, 2024)
Lhok Bubon Beach is a unique coastal area because it has complete biota, namely mangrove forests and macrozoobenthos. This research looks at the composition of mangroves and macrozoobenthos on Lhok Buon Beach. The method used in this research is a survey with three sampling stations. Determination of stations uses purposive sampling with different characteristics and 3 station plots measuring 10x10m. The research results show that the highest macro zoobenthos composition was obtained at station 3 and the lowest at station 1. The diversity index was classified as low, uniformity was medium and high at station 3, and no mangroves dominated at any station. Environmental quality is still relatively good for mangroves and macrozoobenthos